2022
DOI: 10.3390/plants11233297
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and Biomechanics of Peltate Begonia Leaves—Comparative Case Studies

Abstract: Plants are exposed to various external stresses influencing physiology, anatomy, and morphology. Shape, geometry, and size of shoots and leaves are particularly affected. Among the latter, peltate leaves are not very common and so far, only few studies focused on their properties. In this case study, four Begonia species with different leaf shapes and petiole attachment points were analyzed regarding their leaf morphology, anatomy, and biomechanical properties. One to two plants per species were examined. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, no experimental studies have explored the biomechanical aspects of leaf base development under the influence of water currents. Nevertheless, a study of peltate leaf bases, another uncommon trait in Begonia , revealed a complex arrangement of fibers in the petiole, providing increased resistance at the junction point between the leaf blade and its stalk (Rjosk et al, 2022).…”
Section: Platementioning
confidence: 99%
“…However, no experimental studies have explored the biomechanical aspects of leaf base development under the influence of water currents. Nevertheless, a study of peltate leaf bases, another uncommon trait in Begonia , revealed a complex arrangement of fibers in the petiole, providing increased resistance at the junction point between the leaf blade and its stalk (Rjosk et al, 2022).…”
Section: Platementioning
confidence: 99%
“…However, the total of all gradual and/or sudden changes of influencing variables determines whether the transition is smooth or abrupt ( Figure 4 ). In plant leaves, on the one hand, we find superimposed gradual transitions resulting in a damage-resistant transition zone between petiole and leaf lamina [ 63 , 67 , 68 , 69 ]. Moreover, we find abrupt transitions leading to a spatio-temporal controlled shedding of individual plant organs (abscission), such as between branches and petioles resulting in leaf fall in autumn [ 70 , 71 ].…”
Section: Robustnessmentioning
confidence: 99%